A Study of some Mechanical Behavior on a Thermoplastic Material - H, Awham M; Salih, Zaid Ghanem M (Al-Nahrain Journal of Science, 2018)
The aim of the current study is the investigation of mechanical behavior of thermoplastic material type (U-PVC) which may be subjected to effect of some mechanical stresses, because these materials are manufactured to use as drinking water, rainwater and heavy water pipelines. Some tests were carried out on it, included: The (impact, modulus of elasticity (bending), flexural and compression) tests. These tests were performed to determine the ability of the material under study for these stresses. The results which obtained from these tests at natural environments were analyzed and compared with other materials which were used in present studies. These results showed that (Unplasticised PVC, (U-PVC)) material has high impact strength at these ambient, but obviously that there is great effect of notches on this property, as well as that the flexural strength and its ability for sustaining the compression failure is considered suitable if its compared with other materials.